The Role of Growth Hormone in Depression: A Human Model - Algahtany, Mubarak; Sharma, Shubham; Fahoum, Khalid; Jing, Rowan; Zhang, Stanley; Kovacs, Kalman; Rotondo, Fabio; Lee, John; Vanek, Irene; Cusimano, Michael D. (Frontiers in Neuroscience, 2021)
Background Although the relationship between acromegaly and depression has been ascribed to the effects of chronic disease, the role of growth hormone (GH), and insulin like growth factor-1 (IGF-1) is not clear. Objective To determine whether related hormones levels in acromegalics are correlated with depressive symptoms and whether these symptoms are ameliorated following surgery. Materials and Methods A prospective cohort study was conducted on patients diagnosed with acromegaly (n = 15) or non-functioning pituitary adenomas (NFPA; n = 20, as controls) and undergoing first-time surgery, who completed the Center for Epidemiological Studies Depression (CES-D) questionnaire both pre-surgery and post-surgery. The primary outcome was the patient’s severity of depression symptomatology using the CES-D score; GH, IGF-1 levels, and tumor characteristics were also measured. Results Hormone levels (GH and IGF-1) and depression scores in acromegaly patients showed significant reductions following surgery (p < 0.05). The average change in CES-D score was 5.73 ± 2.58 (mean ± SE). A moderate correlation was found between GH levels and CES-D scores (r = 0.52, p < 0.01). The depressed affect subscale accounted for the most improvement in CES-D scores postoperatively and correlated most highly with GH levels. We did not find similar declines in the matched cohort of NFPA patients. Conclusion and Relevance Surgical resection of the pituitary tumor in acromegaly patients leads to reduction in GH levels that is correlated with reduction in CES-D scores. The results suggest a role for GH in depression and provide a stronger foundation on which to build the hypothesis that GH impacts affect. The study also suggests that hormones should be factored into the matrix that entails the neuro-biological underpinnings of depressive disorders. Future work could explore the mechanisms involved, further brain and neuropeptide interactions, and, novel potential therapeutic targets in depressive and other mental health disorders.